Comparative Assessment of Single & Double Interface Shear Strength Properties: A Case Study of a Landfill Project in the Western Cape Province, South Africa - Sylivery, Victor (Department of Civil Engineering, 2023)
Geosynthetics are now stipulated inclusions in municipal solid waste (MSW) landfill's lining systems as they provide a competent hydraulic barrier, limiting environmental pollution and protecting public health. While these inclusions have considerable cost and technical benefits, they have presented several new potential interfaces for shear failure, particularly on side-slopes and basins of conventional hole-in-ground type MSW landfills. In the laboratory, interface shear strength properties of either soil-geosynthetic or geosynthetic-geosynthetic are determined through a single interface testing configuration as per standard testing practices like ASTM D5321 & D6243. However, there is little data on interface shear strength tests conducted through multiple-interface configurations. In addition, conducting single interface shear tests in the laboratory consumes time, effort, resources, and budget, especially when a multi-layered soilgeosynthetic lining system has been proposed. Therefore, this work aimed to ascertain the appropriateness of multiple-interface shear testing in the laboratory by comparing shear strengths mobilised at peak and at large displacements (LD) for single and double testing configurations. Moreover, the interface shear results obtained were applied on a typical side-slope and basal lining system design through the limit equilibrium method (LEM) to understand the implications on factors of safety (FS). In this study, single interface testing configurations constituted only two lining components, either soil-geosynthetic or geosynthetic-geosynthetic. Multiple-interface testing configurations involved direct shearing of three lining components: geosynthetic-geosynthetic-geosynthetic, or soil-geosynthetic-geosynthetic, or soil-geosynthetic-soil, also referred to as double interfaces. The investigated MSW landfill components formed part of the proposed basal lining system for the MSW landfill cell in the Western Cape Province in South Africa. They included three nonwoven geotextiles, two smooth-sided geomembranes, a synthetic cuspate drain, sand, gravelly sand (GS), and leachate collection stone (LCS). All tests were conducted at applied normal pressures of 150, 300, & 450 kPa under saturated conditions with fresh tap water at a 1mm/min shearing rate as recommended by ASTM D5321. The critical interface assessment revealed that failure within the lining components would likely occur at the same interface(s) regardless of the testing configuration. Specifically for this research, both testing configurations, i.e., single and double, involving smooth High-Density Polyethylene (HDPE) geomembrane with nonwoven geotextile combinations depicted the weakest shear resistances. Additionally, this work found that the peak strengths of the critical interface were highest for a double interface testing configuration. Conversely, the LD strengths obtained were either equal or less for a single interface testing configuration. Ultimately, the assessment of both maximum and minimum FS using single and double interface shear results revealed that the former was conservative as it produced lower values of FS. As a result, interface direct shear testing through a double interface configuration enabled an understanding of the dynamics of shear strength transfer among the lining components proposed for the basal lining system of the landfill cell in the Western Cape Province in South Africa.